2000
DOI: 10.1074/jbc.m002782200
|View full text |Cite
|
Sign up to set email alerts
|

The Peroxisome Proliferator-activated Receptor α (PPARα) Regulates Bile Acid Biosynthesis

Abstract: Fibrates are a group of hypolipidemic agents that efficiently lower serum triglyceride levels by affecting the expression of many genes involved in lipid metabolism. These effects are exerted via the peroxisome proliferator-activated receptor ␣ (PPAR␣). In addition, fibrates also lower serum cholesterol levels, suggesting a possible link between the PPAR␣ and cholesterol metabolism. Bile acid formation represents an important pathway for elimination of cholesterol, and the sterol 12␣-hydroxylase is a branch-po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
106
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 148 publications
(110 citation statements)
references
References 32 publications
3
106
1
Order By: Relevance
“…This conclusion is further supported by the competition experiment carried out, which showed that addition of a small amount of recombinant PTE-2 to peroxisomes severely suppresses the activity of BAAT, presumably due to consumption of the substrate CDCA-CoA. PPAR␣ has been established as a key regulator of lipid metabolism, but was also shown to be involved in regulation of bile acid metabolism (38), thus connecting the pathways of bile acid and fatty acid metabolism. Up-regulation of PTE-2 by WY-14,643, together with the PTE-2-mediated suppression of bile acid conjugation with taurine in vitro, could imply that PPAR␣ is also involved in regulating bile acid amidation.…”
Section: Pte-2 Is a Ppar␣ Target Gene That May Regulate Bile Acidsupporting
confidence: 57%
See 1 more Smart Citation
“…This conclusion is further supported by the competition experiment carried out, which showed that addition of a small amount of recombinant PTE-2 to peroxisomes severely suppresses the activity of BAAT, presumably due to consumption of the substrate CDCA-CoA. PPAR␣ has been established as a key regulator of lipid metabolism, but was also shown to be involved in regulation of bile acid metabolism (38), thus connecting the pathways of bile acid and fatty acid metabolism. Up-regulation of PTE-2 by WY-14,643, together with the PTE-2-mediated suppression of bile acid conjugation with taurine in vitro, could imply that PPAR␣ is also involved in regulating bile acid amidation.…”
Section: Pte-2 Is a Ppar␣ Target Gene That May Regulate Bile Acidsupporting
confidence: 57%
“…The role of the PPAR␣ in the fasting-mediated induction of several genes has also been shown (7)(8)(9)(10)38). We examined the effect of fasting on PTE-2 mRNA levels in the PPAR␣-null mouse model, which resulted in a significant increase in PTE-2 mRNA in liver (Fig.…”
Section: Fig 3 Pte-2 Is a Peroxisomal Matrix Proteinmentioning
confidence: 99%
“…Second, the murine and rat sterol 12␣-hydroxylase gene, a branch-point enzyme in the bile salt biosynthetic pathway that determines the ratio of cholic acid to CDCA, is transcriptionally activated through direct binding of PPAR␣ to an imperfect DR1 sequence in the promoter region. Accordingly, treatment of wild-type mice with WY14643 for 1 week resulted in an increased relative amount of CA, an effect that was abolished in PPAR␣ null mice (43). Third, the inducing effects of PPAR␣ ligands on target genes encoding enzymes of fatty acid ␤-oxidation appear to be antagonized in mice by concomitant feeding of a bile salt-enriched diet, suggesting an influence of bile salts on PPAR␣-dependent gene regulation (44).…”
Section: Discussionmentioning
confidence: 99%
“…Similar to Acot15, Acot2 is expressed in the liver, albeit at low levels, and is also expressed in cardiac and skeletal muscle (13)(14)(15)(16)(17), and is upregulated by fasting, streptozotocininduced diabetes, and peroxisome proliferator-activated receptor agonists ( 13,(15)(16)(17). Its major substrates are palmitoyl-CoA (PCoA) and myristoyl-CoA (MCoA) ( 18 ), which positions Acot2 as a potential regulator of longchain fatty acyl-CoA entry into FAO.…”
Section: Bioenergetics Analyses In Isolated Mitochondria and Hepatocytesmentioning
confidence: 99%